2008
DOI: 10.1073/pnas.0803161105
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the phospho-tyrosine signaling machinery in premetazoan lineages

Abstract: Multicellular animals use a three-part molecular toolkit to mediate phospho-tyrosine signaling: Tyrosine kinases (TyrK), protein tyrosine phosphatases (PTP), and Src Homology 2 (SH2) domains function, respectively, as ''writers,'' ''erasers,'' and ''readers'' of phospho-tyrosine modifications. How did this system of three components evolve, given their interdependent function? Here, we examine the usage of these components in 41 eukaryotic genomes, including the newly sequenced genome of the choanoflagellate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
149
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 25 publications
2
149
0
1
Order By: Relevance
“…Similarly, genome data from unicellular metazoan-related lineages is pushing back the times of origin of many gene families formerly believed to be metazoan specific to well into the Proterozoic. Such is the case, for example, of tyrosine kinases (14,50,51), some transcription factors (12,52), membrane-associated guanylate kinases (53), or cadherines (13). The integrin-mediated signaling and adhesion machinery here presented add another striking example to this pattern and suggest that some of these protein families may have emerged even earlier in eukaryote evolution before the divergence of opisthokonts.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, genome data from unicellular metazoan-related lineages is pushing back the times of origin of many gene families formerly believed to be metazoan specific to well into the Proterozoic. Such is the case, for example, of tyrosine kinases (14,50,51), some transcription factors (12,52), membrane-associated guanylate kinases (53), or cadherines (13). The integrin-mediated signaling and adhesion machinery here presented add another striking example to this pattern and suggest that some of these protein families may have emerged even earlier in eukaryote evolution before the divergence of opisthokonts.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, from our study and that done by Abedin and King (13), we can conclude that the major cell-cell and cell-matrix adhesion mechanisms in metazoans, those mediated by cadherins and integrins, respectively, have a deeper evolutionary origin than previously thought. This adds to the growing evidence that major cell signaling and cell adhesion pathways crucial to metazoan development were present in premetazoan lineages (12,50,51,53). Thus, the answers to what triggered the unicellular-to-multicellular transition that gave rise to metazoans may lie not only in the acquisition of new genes but also in the cooption of ancestral proteins into new functions and the evolution of more complex interactions.…”
Section: Discussionmentioning
confidence: 96%
“…The evolution of phosphotyrosine signaling suggests that more than 600 million years ago there was a common ancestor for the unicellular choanoflagellates and for multicellular metazoans, which had already developed this ability (King and Carroll, 2001;King et al, 2008;Peterson and Butterfield, 2005;Pincus et al, 2008). In some species, such as in yeast, tyrosine phosphorylation appears at a very low level, most likely due to promiscuity of serine/threonine kinases (Schieven et al, 1986).…”
Section: The Origin Of Phosphotyrosine Signaling and The Role Of mentioning
confidence: 99%
“…Pincus et al (2) used sequence similarity to identify and enumerate all of the PTKs, PTPs, and SH2 domains in diverse eukaryotic lineages. They found that these genomes could be clearly divided into two groups.…”
Section: An Evolutionary Paradoxmentioning
confidence: 99%
“…Many of these activities are regulated by tyrosine phosphorylation, the covalent addition of a phosphate group to tyrosine residues in cell proteins, and the emergence of this signaling mechanism may actually have been a key enabling event in the transition to multicellularity. Two papers in this issue of PNAS take advantage of genome sequences from diverse eukaryotic lineages to address the origins of the tyrosine phosphorylation signaling machinery; they provide tantalizing insights into more general questions of how complex signaling mechanisms might have evolved (1,2).…”
mentioning
confidence: 99%